2013
DOI: 10.1017/s0959259812000214
|View full text |Cite
|
Sign up to set email alerts
|

Pruritus in older people

Abstract: Pruritus in older people is caused by a wide range of dermatological, systemic, neurological and psychogenic diseases. It can also be attributed to various cutaneous drug reactions. The dermatological, neurological and immunological changes associated with ageing predispose older people to pruritus of a wide range of aetiologies. The most common cause of pruritus in older people is xerosis, or dry skin. Regular use of emollients is the mainstay of treatment for pruritus of any cause, with general measures aimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…It is a complex phenomenon and usually defined as an unpleasant itching sensation which evokes a strong desire to scratch the affected skin at least three times within 2 weeks, lasting more than 5 minutes per episode and persisting for more than 6 weeks (Metz, Grundmann, & Stander, 2011;Zucker, Yosipovitch, David, Gafter, & Boner, 2003). It is also considered a human defense mechanism that may signal underlying diseases or malignancies (Chen & Yesudian, 2013). The prevalence rate of pruritus increases with age, ranging from 40% to 66% (Chen & Yesudian, 2013;Cowdell, 2009;Patel &Yosipovitch, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a complex phenomenon and usually defined as an unpleasant itching sensation which evokes a strong desire to scratch the affected skin at least three times within 2 weeks, lasting more than 5 minutes per episode and persisting for more than 6 weeks (Metz, Grundmann, & Stander, 2011;Zucker, Yosipovitch, David, Gafter, & Boner, 2003). It is also considered a human defense mechanism that may signal underlying diseases or malignancies (Chen & Yesudian, 2013). The prevalence rate of pruritus increases with age, ranging from 40% to 66% (Chen & Yesudian, 2013;Cowdell, 2009;Patel &Yosipovitch, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is also considered a human defense mechanism that may signal underlying diseases or malignancies (Chen & Yesudian, 2013). The prevalence rate of pruritus increases with age, ranging from 40% to 66% (Chen & Yesudian, 2013;Cowdell, 2009;Patel &Yosipovitch, 2010). Shive and colleagues (2013) found that 26% of seven million people who searched for medical care due to pruritus were older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Refer to Table for a list of prescribed medications and medical conditions which are known to cause pruritus and paresthesias without the delusion of an infestation. A patient's medication list and medical history should be carefully reviewed prior to proceeding to the next step of the diagnosis Once it is determined that a patient has both a delusion of an infestation plus the tactile symptoms, the patient likely has DI.…”
Section: Diagnosis and Workupmentioning
confidence: 99%
“…Lynn S. KIMSEY (2,13,18,27,29) X X X Alcoholism (29,30) X X Anemia (13,27,31) X X Autoimmune disease (12, 33) X X Carbon monoxide poisoning (29,35) X X Cancer a (2,13,18,34,36) X X X Cholestasis (2,13,18,27,34,36,37) X X X Cirrhosis (2,34,37) X X Diabetes mellitus (2,13,27,29,34,36) X X X Drug abuse (2,29,36) X Fluoride poisoning (34,38) X X Heavy metal toxicity (29,39) X X Hemochromatosis (34) X Hepatic disease (12, 34) X X Hepatitis B, C (13,27,36) X X X Hyperthyroidism (2,13,27,34,36,…”
Section: Delusional Infestation and Chronic Pruritus: A Reviewmentioning
confidence: 99%
“…These patients suffered from brain cysticercosis, cerebrovascular disease, pernicious anemia, and peripheral neuropathy. Finally, two studies found that more than half of the population over the age of 70 suffers from itch without obvious cause (18,27).…”
Section: Causesmentioning
confidence: 99%